Six Sigma Approach to Developing a Microgrid Station for Research and Teaching - Gabriel Nasser Doyle de Doile; Miguel Castilla; Pedro Paulo Balestrassi; Antonio Carlos Zambroni de Souza; Jaume Miret (IEEE Access)
Design for Six Sigma (DFSS) is a statistical methodology for improving the quality of processes and their organizational areas worldwide used since the 80’s. However, most of the existing laboratories for obtaining experimental results, which validate theoretical proposals that are being studied in the microgrids research field, have been designed without following any roadmap. The purpose of this study was to develop a microgrid station for research and teaching at the Power Electronic Laboratory of Escola Politècnica Superior d Enginyeria de Vilanova i la Geltrú (EPSEVG) based on a DFSS tool called IDDOV, which stands for Identify, Define, Develop, Optimize, and Verify. An IDDOV roadmap to conduct a laboratory design development is provided and applied to design a laboratory at EPSEVG in this study. The results show that a well-structured roadmap, such as IDDOV, promotes a culture of continuous improvement for the microgrid research bed, encouraging feedback from users and stakeholders to identify opportunities for improvement. The conclusion of this paper highlights the benefits of using the DFSS conceptual methodology to develop a microgrid station for research and teaching, such as adaptation to educational needs; enhancement of the learning experience; refutation of experimental errors; cost-effective, flexible, and modular design; collaborative learning environment; data-driven teaching; and continuous improvement. As electrical grids are dynamic systems in constant evolution, a new IDDOV roadmap should be carried out in future studies, to enhance the test bed recommended here.